A Humidity Sensor Based on Silver Nanoparticles Thin Film Prepared by Electrostatic Spray Deposition Process - Thutiyaporn Thiwawong; Korakot Onlaor; Benchapol Tunhoo (Advances in Materials Science and Engineering)
In this work, thin film of silver nanoparticles for humidity sensor application was deposited by electrostatic spray deposition technique. The influence of the deposition times on properties of films was studied. The crystal structures of sample films, their surface morphology, and optical properties have been investigated by X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), and UV-VIS spectrophotometer, respectively. The crystalline structure of silver nanoparticles thin film was found in the orientation of (100) and (200) planes of cubic structure at diffraction angles 2θ  =  38.2° and 44.3°, respectively. Moreover, the silver nanoparticles thin films humidity sensor was fabricated onto the interdigitated electrodes. The sensor exhibited the humidity adsorption and desorption properties. The sensing mechanisms of the device were also elucidated by complex impedance analysis.